Novel technique to repair a bronchopleural fistula after esophagectomy using wide intercostal muscle flap fixed by azygos vein and bronchus: a case report - Yohei Honda; Akihiro Taira; Ayako Hirai; Koji Kuroda; Yoshinobu Ichiki; Fumihiro Tanaka (Surgical Case Reports, 2020)
Abstract Background Post-esophagectomy bronchopleural fistulas can be life-threatening in patients who are exhausted, for example, by surgical stress and pleural infection; therefore, establishment of a reliable surgical procedure is extremely important. We here report a novel procedure entailing muscle flap closure for bronchopleural fistula. Case presentation A 64-year-old man developed a right bronchopleural fistula after esophagectomy. Because he was exhausted by surgical stress and malnourished, we considered reliable surgical closure of the fistula essential. Intraoperatively, it was found to connect with the membranous portion of the right main bronchus. We decided to close the fistula with a pedicled fourth and fifth intercostal muscle flap. After separating the intercostal muscles near the angle of the rib, we passed a muscle flap between the azygos vein and bronchus and sutured it securely to the fistula. The postoperative course was uneventful, and there was no thoracic infection. Postoperative bronchoscopy confirmed the muscle flap had securely closed the fistula. Conclusions The route and suturing technique of the intercostal muscle flap to a fistula are important, especially in exhausted patients.